Optimization of High Early-Strength Concrete Mix Design for Structural Applications in the BJ. Habibie Stadium Construction Project - Firman, Risman; Joey Limbongan; Yanny Febry Fitriani Sofyan; Munadrah; Syahrul Satar; Ahmad Tamsil Yunus; Andi Widiasari Maruddani (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2025)
This study investigates the application of high early-strength concrete (HESC) to accelerate the construction of the west tribune at BJ. Habibie Stadium, which underwent total demolition during a critical project phase. The research employed an experimental method to evaluate the feasibility of materials and optimize the mix design, beginning with small-scale trial mixes at the batching plant and validating the effectiveness of predefined quality control procedures. Aggregate testing was performed on coarse and fine aggregates, including analysis of colloid content, fineness modulus, water absorption, moisture content, and specific gravity. Mix design aimed to achieve a target strength of 30 MPa within 7-day using a water-cement ratio of 0.33 and chemical admixtures (retarder and superplasticizer). Concrete samples were tested for compressive strength at 3 and 7 days. Results showed the 7-day average compressive strength reached 35.19 MPa, confirming the effectiveness of the HESC mix for fast-track construction. Early strength gain was supported by good aggregate gradation and chemical admixture synergy, allowing earlier formwork removal and structural progression. This study concludes that the adoption of optimized HESC provides a viable solution for time-constrained infrastructure projects.